EFEKTIVITAS ONE TO ONE MARKETING PADA ONLINE BANKING - ABEDNEGO, . (Universitas Katolik Widya Mandala Surabaya, 2013)
One to one marketing program is an effort to increase loyalty among marketers and consumers. One to one marketing is not a new thing, it's a matter of a development method and terms of personal marketing. One to one maketing now widely grown and widely applied in many companies today. Not only is it one to one marketing also has a lot of big changes mlakukan changes specifically in order to understand consumers' needs and find appropriate and effective solution to solve the existing problems between the company and its customers. One to one marketing becomes a very helpful thing clients in receiving information and conduct any form of transaction. Not only is it one-to-one marketing is also very beneficial for the bank because it can ascertain the needs of consumers with their data, so that the bank can do with the right form of customer service. The application of one-to-one marketing in the future of online banking is expected over longer able to understand and meet customers' needs and provide customers the ease of doing things in terms of banking.